2017
DOI: 10.7324/ijcrr.2017.9159
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Birth Weight with other Anthropometric Parameters of Newborns in Himachal Pradesh

Abstract: Introduction: Birth weight is an important indicator of child survival. Anthropometric measurements of infant body help us to predict their health and future growth. All the health personal working in child health care should be familiar with normal patterns of growth, so that they can recognize any deviations from the normal range and try to deal with the underlying disorders which could be nutritional, socioeconomic or infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Our present studies revealed OFC to be 34.6±2.2cm. This is in keeping with several studies (Table 3), which estimated OFC to be between 32-36cm [8]. Similar result was obtained by Soni and Kapoor (2017) in their works done which OFC of New borns in Himachal Pradesh was estimated to be 33.58±1.17cm [8].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our present studies revealed OFC to be 34.6±2.2cm. This is in keeping with several studies (Table 3), which estimated OFC to be between 32-36cm [8]. Similar result was obtained by Soni and Kapoor (2017) in their works done which OFC of New borns in Himachal Pradesh was estimated to be 33.58±1.17cm [8].…”
Section: Discussionsupporting
confidence: 91%
“…The size of newborn at birth has been acknowledged as a significant indicator of both fetal and neonatal health. However, size at birth reflects both the duration of gestation and rate of fetal growth [8]. It must therefore be considered with respect to gestational age [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations